Negotiation of the global grid inspection UAV with random delay uncertainty in an information communication network based on a robust fault tolerance mechanism - Shen, Jie; Dong, Wen qi; Wang, Zhi-fang; Wang, Jing; Wang, Yang; Liu, Han min; Li, Haiyan (Frontiers in Aerospace Engineering, 2023)
To accurately simulate the interference mechanism of information communication between unmanned aerial vehicles (UAVs) in the future global grid system, a type of control based on dynamic simulation of the satellite communication network and robust fault tolerance with a stochastic delay uncertain network system is proposed. Based on the imaginary future of the global energy Internet, with unknown information and communication interference, we established a UAV model from sensor to actuator network delay using a robust, fault-tolerant control algorithm and a satellite communication network model that combined the controller’s mathematical model. The simulation results showed improved power transmission capability and communication coverage ability of UAVs by using the network fault-tolerant control mechanism with uncertain network delay and information communication interference. The stability and anti-interference performance was also significantly improved. This algorithm provides a strategy for the future development of global energy Internet.